Pediatrics wards: healing environment assessment / Roslinda Ghazali and Mohamed Yusoff Abbas. - Ghazali, Roslinda; Abbas, Mohamed Yusoff (Universiti Teknologi MARA Cawangan Selangor, 2017)
Malaysian paediatric wards were assessed on their quality status and design trends towards the creation of the healing environment. The objective was to promote best practices in design. PostOccupancy Evaluation (POE) studies were conducted upon paediatric wards in eight hospitals in the Klang Valley. The methodology adopted was the use of UK‟s NHS AEDET and ASPECT Evaluation toolkits, which evaluated the physical qualities and staffs & patients satisfaction levels respectively upon 215 nurses and 217 patients. Results seemed to show the disparity between the positivity of the physical design in relation to users‟ satisfaction. Implications of the findings are discussed.